â€œWork Ethicâ€ Value as Soehartoâ€™s Development Tool in Indonesia - Jaes, Lutfan; Abdul Latiff, Azmi; Ismail, Fadillah; Akmal Damin, Zahrul; Ani, Fauziah; Ani, Fauziah; Rahman Abdul Aziz, Abdul (International Journal of Engineering and Technology, 2018)
This research paper mainly discusses Soeharto and his â€œWork Ethicâ€ value system. It focuses on the role of local wisdom as a fundamental value that has moulded leadership character and style of Soeharto in Indonesia. A term during his leadership tenure was used by Soeharto to identify, list and explain the source of the dominant local wisdom. Content analysis was used as the method of analysis in to explain a series of â€œEnd of the Year Speechâ€, â€œNationhood Speechâ€ and â€œParty Speechâ€. Initial analysis on the speech texts showed that emphasis on values was given at every serie of the speeches delivered. Next, quotations of every paragraph in the speech texts were scrutinized for groupings of dimensions (Value Dimensions) specifically referring to Asian Values. The paragraphs of every text were recited for the final time in order to identify Derived Values originated from each of the Value Dimensions. Recordings of data were carried out by using Archive for Technology, the Life World and Everyday Language. Text Interpretation (ATLAS).ti version 7 software.Â  It was discovered that Soeharto used his â€œNationhood Speechâ€ serie as his main medium to deliver values to his people. Value Dimension â€œWork Ethicsâ€ was identified as the second most important value in his delivery of messages on development. Meanwhile, Derived Values â€œStrong/Kind/Dilligent/Viable/Earnestâ€ were values that frequently appeared in the dimension. At the end of this paper, an explanation on the application of these values in the leadership and development under Soeharto is obtained. In conclusion, a leader who manipulated local wisdom is capable of achieving development that is more pragmatic and effective. Reinvigorating the local wisdom is a significant factor that can catalyze a continuous development specifically in Indonesia and generally in the South East Asia.Â Â